'Benefit at no cost'—should squatters pay rent? A comparative analysis of gain-based awards for trespass in the Common Law and customary Talmudic Law. (3rd April 2017) - Sharon, Avichay
ABSTRACT: This paper focuses on damages awards for trespass. Through a comparison of two legal systems, the Common Law and the customary Talmudic Law, two perspectives emerged. Both traditions provide recourse in the form of gain-based damages awards for the use of another's property without authorisation. However, in the case of trespass, Talmudic law provides for an important exemption from liability where the property owner suffers no loss. Such an exemption is not found in the Common Law. This divergence is explained by the different normative approaches of each of these legal traditions to property rights and especially ownership of land. While both consider the interference with another's property a serious offence, each tradition delineates the scope of these rights differently. The comparison between the two approaches to squatting highlights the problems with one-dimensional translations of customary law concepts in ways that overlook their underlying normative principles and context.